Age and aging effects on blood pressure: 15 years follow‐up of Tehran lipid and glucose study. Issue 6 (15th March 2021) - Khajavi, Alireza; Zayeri, Farid; Ramezankhani, Azra; Nazari, Amir; Azizi, Fereidoun; Hadaegh, Farzad
Abstract: Age is a known predictor of blood pressure (BP); however, the literature mostly includes cross‐sectional investigations. This prospective cohort study aimed to decompose the cross‐sectional and longitudinal age effects on BP. The secondary data were obtained from the Tehran lipid and glucose study, which comprised six repeated measurements of participants, with median follow‐up of 15.8 (interquartile range of 14.2‐16.9) years. The sample is representative of the metropolitan area of Tehran, Iran, containing 7, 460 participants aged 20‐70. The cross‐sectional and longitudinal effects of age (age at baseline and aging, respectively) were fitted in the mixed effects models, taking systolic, diastolic, and pulse BPs as response, adjusting for adiposity, smoking, diabetes, and antihypertensive medication, and stratifying for sex and 10‐year age‐groups. The mean age at baseline was 41.3 (SD = 12.9) years, and 41.7% of the participants were male. Age at baseline and aging were directly associated with BP, aging owned the weaker effect, and the largest distinction were for systolic blood pressure of men aged 40‐49 years (0.75 vs 0.10, p ‐value < .001). Moreover, the aging effects on systolic and diastolic BPs were higher in men than women, in the age groups 40‐49 and 30‐39 years (0.35 vs 0.10 and 0.30 vs 0.07, p ‐values < .001), respectively. Adjusting for adiposity remarkably declined the impact of aging on BP, among the < 50 years old. Abstract : This study decomposed the cross‐sectional and longitudinal effects of age on blood pressure. The longitudinal effect was found to be the weaker effect. The longitudinal effects on blood pressure were higher in men than women.